2020
DOI: 10.1088/1748-9326/ab8495
|View full text |Cite
|
Sign up to set email alerts
|

Root oxygen mitigates methane fluxes in tropical peatlands

Abstract: Tropical peatlands are a globally important source of methane, a potent greenhouse gas. Vegetation is critical in regulating fluxes, providing a conduit for emissions and regular carbon inputs. However, plant roots also release oxygen, which might mitigate methane efflux through oxidation prior to emission from the peat surface. Here we show, using in situ mesocosms, that root exclusion can reduce methane fluxes by a maximum of 92% depending on species, likely driven by the significant decrease in root inputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
1
12
0
2
Order By: Relevance
“…This may be because of the influence of oil palm rhizosphere, as plant rhizosphere and their nitrogen uptake mechanisms have been shown to increase the pH in rhizosphere (Nye, 1981). Similar increases in pH closer to tree and plant stems were also observed in Panamanian peatlands (Girkin et al, 2019) and associated with differences in the concentration and composition of root exudates (Girkin et al, 2018a,b) and oxygen (Girkin et al, 2020b).…”
Section: Discussionsupporting
confidence: 55%
“…This may be because of the influence of oil palm rhizosphere, as plant rhizosphere and their nitrogen uptake mechanisms have been shown to increase the pH in rhizosphere (Nye, 1981). Similar increases in pH closer to tree and plant stems were also observed in Panamanian peatlands (Girkin et al, 2019) and associated with differences in the concentration and composition of root exudates (Girkin et al, 2018a,b) and oxygen (Girkin et al, 2020b).…”
Section: Discussionsupporting
confidence: 55%
“…In non-oil palm peat with fern vegetation, the lignin might has not been decomposed compared to oil palm which has deeper roots. Girkin et al (2020) reported that roots exclude oxygen that affect the decomposition activities. Lignin is a material that is quite resistant to decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between species are significant. Root oxygen mitigates methane fluxes in tropical peatlands (Girkin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its large spatial extent, relatively little is known about greenhouse gas (GHG) emissions from the Cuvette Centrale. Although pristine tropical peatlands are significant sources of methane (CH 4 ) emissions (Girkin et al, 2020) they are usually net carbon sinks (i.e. they accumulate more carbon than the amount of carbon released through decomposition).…”
Section: Peatland Carbon Stocks and Cyclingmentioning
confidence: 99%
“…Second through species-specific adaptations found in flood-tolerant plants in tropical peat swamp forest that increase gas exchange under waterlogged conditions, such as enlarged lenticels (stem pores), the presence of aerenchyma (spongy, porous tissue) and pneumatophores (aerial roots specialised for gas exchange; Pangala et al, 2017). These adaptations can affect fluxes by either increasing oxygenation in the rooting zone, potentially increasing CO 2 production or decreasing CH 4 production, or by providing a physical pathway through which CH 4 , produced belowground, can travel to the atmosphere (Girkin et al, 2020).…”
Section: Studymentioning
confidence: 99%